The Effectiveness of Consuming Young Green Coconut Water on Dysmenorrhea Pain in Adolescent Girls - Wintarsih; Yanti, Eva Nila; Fatiha, Fita; Listiani, Alda; Anita; Ananda (Jurnal Penelitian Pendidikan IPA, 2024)
Dysmenorrhea, characterized by stabbing menstrual pain, affects up to 90% of women globally, impacting adolescent girls' activities and concentration in school. To manage this pain, both pharmacological and non-pharmacological methods are essential. One accessible non-pharmacological method is consuming young green coconut water. This study aimed to assess the effectiveness of young green coconut water in alleviating dysmenorrhea in adolescent girls. Conducted at five junior high schools on Java and Sumatra from May to June 2024, the quasi-experimental study used a pretest-posttest control group design. The population included 126 female students with dysmenorrhea, with a sample of 56 divided into experimental and control groups. Data were collected using the Numeric Rating Scale (NRS) and analyzed. Results showed that the mean menstrual pain before intervention was 5.18 (moderate pain) in the experimental group and 4.68 (moderate pain) in the control group. Post-intervention, the experimental group's mean pain was 1.00 (mild pain), while the control group's was 3.43 (mild pain). Statistical analysis indicated significant pain reduction in the experimental group (p = 0.000). The study concluded that young green coconut water effectively reduces dysmenorrhea pain in adolescent girls. Schools are encouraged to educate students about non-pharmacological pain management methods like this.